Assessment of the critical period for the effect of intercepted solar radiation on sunflower oil fatty acid composition - Echarte, Maria Mercedes (2013)
The fatty acid composition of sunflower (. Helianthus annuus L.) oil closely depends on the environmental conditions during grain filling. Temperature and solar radiation are the main environmental factors driving oil fatty acid composition. Minimum night temperature and intercepted solar radiation per plant (ISR) during grain filling independently affect oleic acid percentage of traditional sunflower oil. Critical period for temperature effect on this trait has been shown to be placed between 100 and 300. °C day after flowering (°Cd. af). The period of maximal sensitivity of fatty acid composition to ISR remains unknown. The aim of the present work was to identify the time window of high sensitivity (critical period) of fatty acid composition to ISR of sunflower oil. For this, ISR was modified by shading (50% or 80%) or thinning (50%) field grown sunflower hybrid DK3820 during different periods of grain filling. The timing of maximal sensitivity of fatty acid composition to source variations during post flowering periods was explored and analyzed by two widely used approaches: (i) evaluation of the relative oleic acid percentage under short shading treatments in relation to the control and (ii) window-pane analysis of the response of oleic acid percentage to ISR. The first approach generated differing estimates of the critical period depending on the level of radiation reduction. Using the second approach, a developmental interval during which oleic acid was most sensitive to ISR regardless of the radiation level was determined. The critical period began at 350. °Cd. af and ended at 450. °Cd. af. The critical period for radiation effect on oleic acid concentration differed from that of the radiation effect on grain weight and oil concentration and from the critical period for temperature effect on oil fatty acid composition. Different critical periods for different traits and specific environmental factors are indicative of the complexity of the interaction between environmental conditions and grain growth and oil synthesis dynamics.